2011
DOI: 10.4134/jkms.2011.48.5.1083
|View full text |Cite
|
Sign up to set email alerts
|

Spacelike Maximal Surfaces, Timelike Minimal Surfaces, and Björling Representation Formulae

Abstract: Abstract. We show that some class of spacelike maximal surfaces and timelike minimal surfaces match smoothly across the singular curve of the surfaces. Singular Björling representation formulae for generalized spacelike maximal surfaces and for generalized timelike minimal surfaces play important roles in the explanation of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…Non-trivial minimal surfaces in L 3 are also available in the literature (see e.g. [35][36][37] for Lorentzian helicoids and catenoids). However, these are embedded in a non-trivial way in the time-like direction and hence most of these surfaces do not preserve a one parameter family of isometries of the ambient space-time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-trivial minimal surfaces in L 3 are also available in the literature (see e.g. [35][36][37] for Lorentzian helicoids and catenoids). However, these are embedded in a non-trivial way in the time-like direction and hence most of these surfaces do not preserve a one parameter family of isometries of the ambient space-time.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the only non-vanishing component of the Ricci tensor is 37) and that the Ricci scalar is zero,…”
Section: Plane Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The spacelike helicoids and the timelike helicoids match analytically across their folded singularities, which is a general property of folded singularities of analytic surfaces with zero mean curvature [1,2].…”
Section: Preliminariesmentioning
confidence: 98%
“…Moreover, these surfaces often can be real analytically extended to ZMC surfaces which have more than one causal character. For example, motivated by the works [8,9,10,12,13], in [6], Fujimori et al showed that any maxface which has non-degenerate fold-singularities [6, Definition 2.13] is extended real analytically to a timelike minimal surface. In this extension, the set of fold singularities of the maxface forms a non-degenerate null curve on a ZMC surface, where a non-degenerate null curve is a regular curve whose velocity vector field is lightlike and not proportional to its acceleration vector field everywhere.…”
Section: Introductionmentioning
confidence: 99%